Methane Emission Factors for Rice Production in the Mekong River Delta - Yen, Bui Tan; Wassmann, Reiner; Sander, Björn Ole (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
This is an info note elaborating on a study of the International Rice Research Institute (IRRI) conducted by Vo et al. (2018) on methane emission from rice cultivation in different agro-ecological zones of the Mekong River Delta, focusing on seasonal patterns and emission factors for baseline water management.